ANALISIS PERBEDAAN GENRE GAME PADA GOOGLE PLAY MENGGUNAKAN FRAMEWORK OCTALYSIS - Tobing, Dema Mathias Lumban (STMIK Palangkaraya, 2019)
Android-based games are divided into various genres so that there are many variations of the game that can be played but many game developers don't know how to develop games based on the player's perspective that is closely related to human computer interaction. The purpose of this study was to find out the strongest characteristics of player motivation in each genre available on Google Play using Octalysis framework based on design and gameplay so that differences in player motivation were found. The Octalysis Framework has been used by many companies to make gamification products, because in gamification there are game elements so that they can be used to analyze game products. With this research, it is expected that each genre has the strength of characteristics and weaknesses as a benchmark of data for developers and game designers to create more varied games.